(untitled) (Tạp chí Y học Cộng đồng, 2026)
Introduction: Rehabilitation of the atrophic posterior maxilla often requires sinus floor elevation to achieve adequate bone height. Magnetic mallet technology, a recent innovation in implant site preparation, offers a minimally invasive alternative to conventional drilling by condensing bone while preserving its vitality. This case report describes the staged management of a patient with cystic lesions involving teeth #16 and #17, subsequent sinus augmentation, and implant placement using the magnetic mallet (Osseotouch, Italy). Case Presentation: A 43‑year‑old female presented with purulent cystic lesions associated with teeth #16 and #17 and reactive sinus involvement. Initial treatment comprised extraction of the affected teeth, cyst enucleation, and placement of a calcium‑phosphate graft. After ten months, residual bone height was around 2 mm, necessitating lateral sinus floor elevation with bone grafting and a platelet‑rich fibrin (PRF) membrane. Four months later, cone‑beam computed tomography confirmed adequate bone dimensions. Implants were placed using a magnetic mallet with osteotomic inserts, achieving good primary stability. Final restorations were metal‑free crowns. Conclusion: The staged approach combining cyst enucleation, sinus augmentation with PRF, and magnetic mallet‑assisted implant placement resulted in successful functional and aesthetic restoration. The magnetic mallet allowed conservative, heat‑free bone preparation, contributing to favorable implant stability and healing.